Amplifying Students’s Understanding of the Basic Concept of the Periodic Table through Wordwall in the Coastal School of Riau Islands - Natasha Febiana; Fitriani Putri; Hutajulu Ezra Solafide; Pohan Anggi Amanda (SHS Web of Conferences)
Learning media has an important role in reinforcing chemistry materials, especially the periodic table. The study aims to develop Wordwall as an educational media in strengthening the understanding of the periodic system table in coastal school. The study uses Research and Development with the ADDIE research method until the implementation stage. This media was validated by 2 lecturers of Chemistry Education at Raja Ali Haji Maritime University. From the material expert, the results obtained were 92.5% with very valid information, while from the media expert, 75% was obtained with valid information in the first stage and 85% with very valid information in the second stage. Meanwhile, the results of teacher practicality obtained 83.33% with a very valid statement and the results of student practicality with two aspects, the effectiveness aspect obtained 81.42% with a very effective statement and the attractiveness aspect obtained 77.33% with an interesting statement. With this research, it can be concluded that the learning media for strengthening understanding of the periodic table is very valid, very effective, and interesting to use in the learning process in coastal schools in the Riau Islands.